Religious Fundamentalism: Threats on Religious Life in West Sumatera-Indonesia - Novi Hendri; Ridha Ahida; Hardi Putra Wirman (AJIS: Academic Journal of Islamic Studies, 2021)
This study aims to describe religious fundamentalism problems. Radicalism movement is caused by textual religious understanding and social as well political condition that are not conducive to the religious fundamentalism group. The finding of this research indicated that religious fundamentalism has transformed into radical and terrorism movement. The transformation of religious understanding from fundamentalism, radicalism, to terrorism is triggered by the dissatisfaction of radical group on the government, in terms of economic and political condition as well law enforcement activities. This research also indicated that religious radicalism group spreads the ideology by using mosque as the basis of their movement as well as educational institution. Mosque is also considered as power relation by religious radicalism group. This research was conducted through interviews and Focus Group Discussions with organizations and religious leaders categorized as Religious Fundamentalism